Oral hygiene as a cardiovascular risk factor - review of the literature - Chiżyński, Adam; Łęgocka, Weronika; Andryszczak, Paweł (Journal of Education, Health and Sport, 2023)
Introduction and Objective. Cardiovascular diseases are the main cause of death in Poland and around the world. An important aspect of managing patients with cardiovascular diseases is their proper diagnosis and treatment. An important element is also the prevention of cardiovascular diseases. Prevention of the occurrence of cardiovascular diseases mentioned above consists of the elimination of so-called cardiovascular risk factors. A relatively unknown risk factor for cardiovascular disease is the lack of oral hygiene. The authors of the work analyze what elements are related to the lack of oral hygiene affect the cardiovascular risk and try to present the mechanisms of the oral cavity condition that may affect the cardiovascular system. Review Methods. A review of the recent literature was conducted using PubMed, Google Scholar databases. Brief description of the state of knowledge. The oral cavity is a site colonised by many species of microorganisms.Bacteria from periodontal pockets can travel to other systems as well as enter the bloodstream, and that way to distant organs. A normal endocardial endothelium provides a barrier for bacteria and prevents colonisation and the development of inflammation. However, in cases where it is damaged, it can provide a gateway for microorganisms to infect the valve, which may lead to the development of infective endocarditis. Summary. In case of periodontitis in patient with ischemic heart disease, myocardial infarction or stroke, active dental or periodontal treatment should be undertaken. Bacteria from periodontal pockets can travel to other systems causing pathological changes in them. Key words Oral hygiene, periodontitis, infective endocarditis